2017
DOI: 10.1038/ja.2016.167
|View full text |Cite
|
Sign up to set email alerts
|

Trachyspic acid 19-butyl ester, a new inhibitor of Plk1 polo box domain-dependent recognition from uncharacterized fungus RKGS-F2684

Abstract: Polo-like kinase 1 (Plk1) is a serine-threonine protein kinase that possesses many essential functions during mitosis and is one of the key regulators of mitotic cell division. 1,2 Although it has a catalytic domain of protein kinase at its N-terminus, it possesses a phosphopeptide binding domain named polo box domain (PBD) at its C-terminus. 3,4 PBD binds to other protein in a phosphorylation dependent manner. PBD-dependent binding not only is important for the subcellular localization, but is also necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…It also showed an excellent specificity profile for Plk1 (Ki=0.012±0.001 µM) over other two kinases, Plk2 (Ki=5.5±0.7 µM) and Plk3 (Ki=3.7±0.2 µM). This study provided an excellent opportunity to design Plk1 inhibitors targeting both functional and enzymatic domains to overcome the specificity of ATP-competitive kinase inhibitors 84. Chen et al also reported 5-(ethylsulfonyl)-2-(4-fluorophenyl)-4-(phenylsulfonyl) oxazole (T521)…”
mentioning
confidence: 90%
“…It also showed an excellent specificity profile for Plk1 (Ki=0.012±0.001 µM) over other two kinases, Plk2 (Ki=5.5±0.7 µM) and Plk3 (Ki=3.7±0.2 µM). This study provided an excellent opportunity to design Plk1 inhibitors targeting both functional and enzymatic domains to overcome the specificity of ATP-competitive kinase inhibitors 84. Chen et al also reported 5-(ethylsulfonyl)-2-(4-fluorophenyl)-4-(phenylsulfonyl) oxazole (T521)…”
mentioning
confidence: 90%
“…Polo-like kinase 1 (Plk1) is a serine-threonine protein kinase involved in the regulation of mitotic cell division and often overexpressed in various malignancies. The C terminus of Plk1 has polo-box domain (PBD), which is essential for interaction with other proteins and subcellular localization (Nogawa et al., 2017). A metabolite named trachyspic acid 19-butyl ester ( 17 ) (Figure 5) along with trachyspic acid was isolated from uncharacterized fungus RKGS-F2684 (Nogawa et al., 2017).…”
Section: Selected Inhibitors Of Human Heparanasementioning
confidence: 99%
“…The C terminus of Plk1 has polo-box domain (PBD), which is essential for interaction with other proteins and subcellular localization (Nogawa et al., 2017). A metabolite named trachyspic acid 19-butyl ester ( 17 ) (Figure 5) along with trachyspic acid was isolated from uncharacterized fungus RKGS-F2684 (Nogawa et al., 2017). Trachyspic acid 19-butyl ester and trachyspic acid showed inhibition toward PBD-dependent binding with an IC 50 value of 102 and 128 μM, which was comparable with purpurogallin (IC 50 : 114 μM), which served as positive control (Nogawa et al., 2017).…”
Section: Selected Inhibitors Of Human Heparanasementioning
confidence: 99%
See 1 more Smart Citation
“…Furanones and their fused frameworks are versatile heterocyclic moieties that exist in many natural products [1,2] and biologically active compounds [3]. In particular, 2,2-di substituted furanone core is present in many natural products such as Pseurotin A [4], Hyperolactone C [5,6], Trachyspic acid [7,8], Jatrophone [9], Eremantholide A [10], Cephalimysin A [11], Geiparvarin [12,13], Bullatenone [14] Griseofulvin [15] and have been discovered to possess a broad range of medicinal applications [3] and also used for the synthesis of fluorescent materials [16].…”
Section: Introductionmentioning
confidence: 99%